Levels of Polycyclic Aromatic Hydrocarbons (PAHs) in muscles of commercial fishes from Iraqi waters - Al-Imarah, F.J.M.; Nasir, A.M.; Al-Timari, A.A.K.; Al-Anbar, L.J.M. (Mesopotamian Journal of Marine Sciences, 2022)
The concentrations of polycyclic aromatic hydrocarbons (PAHs) were measured in the muscles of eight kind of fishes from National Iraqi Waters, Five marine species viz., Euryglossa orientalis, Otolithes ruber, Lethvinus nebulosus, Epinephelus coioides and Johnieops sina which were collected from Iraqi marine waters, and three species viz, Cyprinus carpio, Carasobarbus luteus and Plantiliza abu which were collected from Shatt Al-Arab river fresh water. All fishes were collected during spring and autumn seasons within the year 2015. Recorded total polycyclic aromatic hydrocarbons in fish species from Iraqi national waters were varied between 0.054 and 155.44 ng/g, while for individual fishes: Anthracene recorded the highest values varied between 17.629 and 155.44 ng/g dry wet. Lower total PAHs value recorded was 197.54 ng/g dry wet. in O. ruber and higher total PAHs value recorded was 381.415 ng/g dry wet. in E. coioides, followed by P. abu which recorded higher total PAHs value of 275.938 ng/g dry wet. Large differences in the values of PAHs recorded during autumn 2015 were achieved which were lower than those recorded during spring. According to the ratios between low and high molecular weight PAHs, there are two sources for PAHs in the investigated fishes, the first was pyrogenic which was appeared in the fishes L. nebulosus and E. orientalis only for 0.355 and 0.274 ng/g respectively during spring 2015 and second anthrapogenic which appeared in all fishes except L. nebulosus and E. orientalis. Therefore during spring season the dominated source was the anthropogenic one. For the results of Autumn season, the ratios indicate predominant the values which were lower than 1 for mostly all studied fishes except that for E. orientalis which was equal to 1.040 indicating that most of the PAHs were from anthropogenic source. Although, concentration of petroleum hydrocarbons (PAHs) in fishes from national Iraqi waters along North West Arabian Gulf were recorded in most studied fishes, but they markedly higher than that in the background and previously reported studies in the same and nearby areas. From a public health point, petroleum hydrocarbon residue levels, especially the carcinogenic ones, in all fish samples analyzed in this study are considerably lower than the hazardous levels and doesn’t exert any health effect upon human being upon consumption.